NIR-responsive carbon-based nanocarriers for switchable on/off drug release and synergistic cancer therapy. Issue 47 (6th November 2018) - Nie, Rongrong; Liu, Hongji; Hu, Lin; Gu, Xinyu; Qian, Junchao; Wang, Hui
Abstract : This communication reports a chitosan-gated carbon-based nanocarrier as a NIR light-switchable drug delivery system for controlled on/off drug release. Abstract : Herein, we present a light-switchable drug delivery system based on chitosan-gated carbon-based nanocarriers (CGC NCs) that exhibit a loading capacity for doxorubicin as high as ∼89.65 wt% and controlled on/off release with/without NIR irradiation. In vitro and in vivo results show that the CGC NCs manifest high efficacy for cancer therapy through a synergistic effect of combined chemo-photothermal treatment.